Market fluctuations and country risk relationships for Australian and Indian energy - Simpson, John (Springer New York LLC, 2013)
Indians and Australians have a great deal more in common than a love of the game of cricket. A recent Australia–India energy and minerals forum (Australian Ministry for Foreign Affairs and Trade 2010) acknowledged that there exists a mutual respect for democracy and the rule of law. In both countries pluralism and human rights are important social objectives. Australia and India are cooperating increasingly on matters relating to trade and investment, international security, climate change, science and education, but also in the areas of resources and energy. The forum made the point that India is soon to become Australia’s third largest export market, after China and Japan (e.g., two-way trade between India and Australia had grown to 22 billion dollars in 2008–2009).